Sharing or Not: Psychological Motivations of Brand Rumors Spread and the Stop Solutions - Zhang, Xu; Zhu, Hong; Huang, Yu; Xiao, Chunqu (Frontiers in Psychology, 2022)
Brand rumours can harm brands' image and bring significant impacts on customers' decision-making and sharing behaviour. Finding practical strategies for preventing the spread of brand rumours continues to be a challenge. Building on the social contagion theory, the current research enriches the discussion on understanding why people spread rumours and how to deal with the spreading of rumours. Sharing brand rumours is motivated by a variety of complex psychological reasons, but prior research didn't adequately analyse the problem from a complexity perspective. Therefore, using a sample of 416 interviewers within eight types of brand rumours, this study employs fuzzy-set qualitative comparative analysis (fsQCA) to investigate the combination of rumour psychological communication motivations in brand activities and solutions to prevent the spread of brand rumours. The current study discoveries three and two first-level configurational solutions, respectively, that can promote positive and negative rumour spreading. To summarize, emotional stimulation is a key component in the spread of rumours; altruism and relationship management motivation can coexist at times; and untrusted rumours are disseminated through other motivation factors. Solutions to prevent rumours from spreading are also provided. Furthermore, the findings help to understand the psychology of configurational motivation and how it can help brands reduce the spread of brand rumours. Finally, these discoveries' theoretical contributions and practical implications are presented.